The Effectiveness of Content Mastery Services with Internet-Based Problem Based Learning Models in Enhancing Student Critical Thinking Skills - Amrina Asfarina; Marjohan Marjohan; Riska Ahmad (Universitas Negeri Padang, 2019)
The development of information and communication technology has a gross impact on all aspects of life, including education. Therefore it provides convenience and flexibility in exploring science. However, information in Internet is not always verified. Therefore critical thinking is highly needed in dealing with these developments. The objective of this research was to determine the improvement of students' critical thinking skills after participating in content mastery services with Internet-based problem learning models. This study is a Quasi-Experiment which uses quantitative methods and The Non-Equivalent Control Group Design. The subjects of this study were students of Public High School 2 in Padang. Furthermore, the research instrument used was a Likert model scale. Data analysis was performed with the aid of the Wilcoxon Signed Ranks Test and the Kolmogorov-Smirnov Two Independent Sample test. According to the research, content mastery services with Internet-based problem learning models are effective for improving students' critical thinking skills.